2014
DOI: 10.2141/jpsa.0130132
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Low-Fibre Sunflower (<i>Helianthus annus </i>L.) Meal as Substitute of Soybean Meal in Turkey Rations: Effects on Growth Performance and Meat Quality

Abstract: Soybean meal (SBM) is the most widely and expensive protein source used in the formulation of poultry diets; however, when the price of SBM increases, poultry nutritionists seek alternative sources that are more economical in formulating least-cost rations. This research aimed to evaluate the effects of air classified sunflower meal (SFM) in diets of turkeys on their growth performance, carcass yields and meat quality. A total of 140 1-d-old female turkeys (Nicholas 500) were randomly assigned to two dietary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(30 reference statements)
0
14
1
Order By: Relevance
“…Similar values were observed in present experiment. Laudadio et al (2014) ) in legs and breast were 1.1 and 0.5 (Baggio et al, 2002). In comparison with current results, Karakök et al (2010) presented higher contents of DM, protein, ash and lower content of fat in thigh muscles.…”
Section: Nutritional Compositioncontrasting
confidence: 71%
“…Similar values were observed in present experiment. Laudadio et al (2014) ) in legs and breast were 1.1 and 0.5 (Baggio et al, 2002). In comparison with current results, Karakök et al (2010) presented higher contents of DM, protein, ash and lower content of fat in thigh muscles.…”
Section: Nutritional Compositioncontrasting
confidence: 71%
“…gizzard, liver, pancreas, and spleen) and cecal pH (P >0.05). Laudadio et al (2014b) found that the substitution of SBM with micronized air-classified SFM (172 g/kg) as the main protein source had no adverse effect on growth performance and dressing percentage, and improved the breast and thigh muscle relative weights of the turkeys. Alagawany et al (2017) observed that increasing dietary inclusion of sunflower meal (0%, 25%, 50%, and 75% replacing SBM) in broiler diets negatively influenced abdominal fat percentage.…”
Section: Resultsmentioning
confidence: 93%
“…Sunflower meal (SFM), a byproduct obtained after oil extraction form sunflower seeds. Sunflower meal (SFM) is relatively cheaper source of protein and serves as suitable alternative to SBM as protein source in poultry feed formulation [3] [5], because of its good protein level, high contents of calcium, phosphorus, vitamin B-complex, and low levels of antinutritional and toxic compounds [4] [6]. The crude protein level of SFM varied from 29 to 45%, depending upon the oil extraction and dehulling process and remain inverse to fiber contents [5] [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower meal (SFM) is relatively cheaper source of protein and serves as suitable alternative to SBM as protein source in poultry feed formulation [3] [5], because of its good protein level, high contents of calcium, phosphorus, vitamin B-complex, and low levels of antinutritional and toxic compounds [4] [6]. The crude protein level of SFM varied from 29 to 45%, depending upon the oil extraction and dehulling process and remain inverse to fiber contents [5] [7,8]. Yet, high level of insoluble fiber and low level of limiting essential amino acids (lysine and methionine), are limiting factors for the use of SFM in poultry diet [2] [3].…”
Section: Introductionmentioning
confidence: 99%